2016
DOI: 10.4209/aaqr.2015.04.0255
|View full text |Cite
|
Sign up to set email alerts
|

Black Carbon Aerosols at Mt. Muztagh Ata, a High-Altitude Location in the Western Tibetan Plateau

Abstract: Measurements of equivalent black carbon (EBC. The diurnal variation in all seasons was stable throughout the day but slightly increased during the nighttime. The results of the potential source contribution function analysis indicated four potential source areas for EBC, with the contributions of polluted trajectory clusters ranging from 4% to 50%. High EBC concentrations were found to be associated with regional circulations developed in high aerosol optical depth areas, resulting in recirculation and accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
(72 reference statements)
2
10
0
Order By: Relevance
“…A comparison of the BC or EC measured at different locations is given in Table . The concentrations of BC in the Himalayas apparently decrease sharply with altitude; for example, BC concentrations measured at Lulang were significantly higher than the values reported from Nam Co [ Ming et al ., ], QSS station [ Zhao et al ., ], Hanle [ Babu et al ., ], NCO‐P [ Marinoni et al ., ], and Muztagh Ata [ Zhu et al ., ]. However, the concentrations of BC in urban sites located within high‐altitude basins, as in Lhasa [ Gao et al ., ], can be 5 times higher than that in Lulang.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the BC or EC measured at different locations is given in Table . The concentrations of BC in the Himalayas apparently decrease sharply with altitude; for example, BC concentrations measured at Lulang were significantly higher than the values reported from Nam Co [ Ming et al ., ], QSS station [ Zhao et al ., ], Hanle [ Babu et al ., ], NCO‐P [ Marinoni et al ., ], and Muztagh Ata [ Zhu et al ., ]. However, the concentrations of BC in urban sites located within high‐altitude basins, as in Lhasa [ Gao et al ., ], can be 5 times higher than that in Lulang.…”
Section: Resultsmentioning
confidence: 99%
“…The ATN data from the Aethalometer™ are converted to BC mass by assuming a fixed BC specific attenuation cross section of 16.6 m 2 g −1 [ Virkkula et al ., ]. Details of the instrument's operating principles have been presented elsewhere [ Cao et al ., , ; Zhu et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…The EC and OC levels in KY were also significantly above the mean values, reported by Lim et al (2003), at the background Pacific Ocean (0.09 and 0.21 µg m -3 , respectively), Asian-influenced Pacific Ocean (0.29 and 0.70 µg m -3 ), offshore of Japan (0.27 and 1.00 µg m -3 ) and Sea of Japan (0.66 and 2.43 µg m -3 ). Our EC levels were somewhat higher than the equivalent black carbon (EBC, optical method) reported for a Western Tibetan Plateau site which had the daily levels varying from 33.6 to 330.2 ng m -3 (Zhu et al, 2016) and indeed were much above the EBC levels measured at the South Pole (monthly EBC < 8 ng m -3 ) reported in Sheridan et al (2016). The EC and OC results thus showed that even the KY site was in a relatively remote forest area of Thailand the effects of human activities on pollution levels were still clearly shown as compared to other more "truly" remote areas in Asia reported by Lim et al (2003) or the South Pole (Sheridan et al, 2016).…”
Section: Ec and Oc Compositionmentioning
confidence: 88%
“…Although the PSCF model is a practical tool often used to locate potential source areas (e.g., Zhang et al, 2013b;Dimitriou, 2015;Zhu et al, 2016), a restriction of this method is that the same PSCF values may occur in different grid cells when BC loadings at the receptor site are either substantially larger or only slightly larger than the criterion value, which is often derived as the arithmetic mean (e.g., Wang et al, 2004;Xu and Akhtar, 2010;Zhao et al, 2015). This may lead to difficulties in differentiating heavy pollution sources from moderate ones.…”
Section: Bc Potential Pollution Source Areasmentioning
confidence: 99%